Review of Winged Stallions and Wicked Mares: Horses in Indian Myth and History. By Wendy Doniger - Sojkova, Barbora (JAOS, 2022)
Winged Stallions and Wicked Mares: Horses in Indian Myth and History. By Wendy Doniger. Charlottesville: University of Virginia Press, 2021. Pp. 300. $35.